The Effect of Greater Occipital Nerve Block on Chronic Migraine - Safiabadi, Mahdi; Tayebi, Sirous; Heshmatifar, Mahdi (International Clinical Neuroscience Journal, 2017)
Background: Greater occipital never block has been shown to be an effective treatment in patients with cluster or tension type headache but there are very few studies investigating its effect in patients with chronic migraine. This study was to determine the effectiveness of greater occipital never block on headache in patients with chronic migraine. We designed an interventional before-after study for patients suffered from chronic migraine. Methods: Patients were participated in this study according to inclusion and exclusion criteria. Frequency, severity and duration of headaches were recorded by patients 2 weeks before injection and then during 6 weeks after injection. We compared data recorded before injection to data from each two-week after injections to determine the effectiveness of greater occipital never block in improvement of headaches in patients with chronic migraine. Results: Fourteen patients (mean age=34.21±2.75) were included in the study. Number of attacks was significantly decreased during 6 weeks follow up (p<0.05). Mean headache severity was significantly decreased during first and second two-week follow up by 3.04 and 2.39 points, respectively. Duration of headaches was not significantly reduced during follow up. Conclusion: In conclusion, Greater occipital nerve block can improve the status of headache in patients with chronic migraine by decreasing the severity and frequency of headaches. However, it may not be effective in shortening the duration of headaches.